Photovoltaic activity in a ZnSe/PEO-chitosan blend electrolyte junction - Mohamad, Souad A.; Ali, Moazzam H.; Yahya, Rosiyah; Ibrahim, Zainol Abidin; Arof, Abdul Kariem (Institute for Ionics, 2007)
Abstract Thin films of ZnSe and PEO–chitosan blend polymer doped with NH4I and iodine crystals were prepared to form the two sides of a semiconductor electrolyte junction. ZnSe was electrodeposited on indium tin oxide (ITO) conducting glass. The polymer is a blend of 50 wt% chitosan and 50 wt% polyethylene oxide. The polymer blend was complexed with ammonium iodide (NH4I), and some iodine crystals were added to the polymer–NH4I solution to provide the I−/I3−redox couple. The room temperature ionic conductivity of the polymer electrolyte is 4.32×10−6 S/cm. The polymer film was sandwiched between the ZnSe semiconductor and an ITO glass to form a ZnSe/polymer electrolyte/ITO photovoltaic cell. The open circuit voltage (Voc) of the fabricated cells ranges between 200 to 400 mV and the short circuit current between 7 to 10 μA.